2019
DOI: 10.1016/j.ejso.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Resection margins and local recurrences in breast cancer: Comparison between conventional and oncoplastic breast conserving surgery

Abstract: Background: This retrospective cohort study aims to compare surgical margins, reoperations and local recurrences after conventional or oncoplastic breast conservation surgery (BCS). Furthermore, we aim to investigate differences between various oncoplastic techniques. Material and methods: We reviewed 1800 consecutive patients with primary invasive breast cancer (N ¼ 1707) or ductal carcinoma in situ (N ¼ 93) who underwent BCS at Helsinki University Hospital between 2010 and 2012. Results: Conventional BCS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
4
34
0
2
Order By: Relevance
“…Although no long-term differences in recurrence rates and survival between BCS and OPS have been reported 13,19,22,[43][44][45] , current evidence regarding the impact of OPS on the re-excision rate is limited because the data are from single-centre studies with relatively few patients undergoing OPS (ranging from 31 to 1177), and in most studies the methodology was weak 11,13,44,[46][47][48] . The present results are in line with a meta-analysis 19 from 2018 that found a significantly lower risk of re-excision in patients who underwent OPS compared with those who had BCS (relative risk 0⋅66, 95 per cent c.i.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no long-term differences in recurrence rates and survival between BCS and OPS have been reported 13,19,22,[43][44][45] , current evidence regarding the impact of OPS on the re-excision rate is limited because the data are from single-centre studies with relatively few patients undergoing OPS (ranging from 31 to 1177), and in most studies the methodology was weak 11,13,44,[46][47][48] . The present results are in line with a meta-analysis 19 from 2018 that found a significantly lower risk of re-excision in patients who underwent OPS compared with those who had BCS (relative risk 0⋅66, 95 per cent c.i.…”
Section: Discussionmentioning
confidence: 99%
“…Oncoplastic surgery (OPS) improves cosmetic outcomes and is nowadays used in up to 34 per cent of patients with breast cancer undergoing BCS [10][11][12][13][14] . Previous studies 15,16 have demonstrated that by using OPS breast conservation becomes an alternative to mastectomy in patients with large and multifocal tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The indications for every oncoplastic technique are different and various algorithms have been devised to assist with the decision process. [2][3][4] The choice is based on tumour and breast characteristics, extent of resection, previous surgery and expectations and wishes of the patient. [2][3][4] However, a 'good surgical hand' in oncoplastic techniques is not enough to optimize the oncological and aesthetic results!…”
mentioning
confidence: 99%
“…First, the use of steroids in patients with amoebic colitis on the presumptive diagnosis of inflammatory bowel disease can lead to toxic megacolon and perforation. 3 Second, it has been found that the use of Loperamide, which is very commonly used in cases of diarrhoea, will increase the chance of developing fulminant amoebic colitis. 4…”
mentioning
confidence: 99%